Bioleaching and Electrochemical Behavior of Chalcopyrite by a Mixed Culture at Low Temperature - Peng, Tangjian; Liao, Wanqing; Wang, Jingshu; Miao, Jie; Peng, Yuping; Gu, Guohua; Wu, Xueling; Qiu, Guanzhou; Zeng, Weimin (Frontiers in Microbiology, 2021)
Low-temperature biohydrometallurgy is implicated in metal recovery in alpine mining areas, but bioleaching using microbial consortia at temperatures < 10°C was scarcely discussed. To this end, a mixed culture was used for chalcopyrite bioleaching at 6°C. The mixed culture resulted in a higher copper leaching rate than the pure culture of Acidithiobacillus ferrivorans strain YL15. High-throughput sequencing technology showed that Acidithiobacillus spp. and Sulfobacillus spp. were the mixed culture's major lineages. Cyclic voltammograms, potentiodynamic polarization and electrochemical impedance spectroscopy unveiled that the mixed culture enhanced the dissolution reactions, decreased the corrosion potential and increased the corrosion current, and lowered the charge transfer resistance and passivation layer impedance of the chalcopyrite electrode compared with the pure culture. This study revealed the mechanisms via which the mixed culture promoted the chalcopyrite bioleaching.